Outstanding leadership in primary education: Perceptions of school leaders in English primary schools. (April 2020) - Dhillon, Jaswinder K; Howard, Colin; Holt, Jayne
The nature of leadership and management in a school are key to achieving high-quality education for all pupils. Leadership theories and empirical research have sought to identify characteristics of leaders, aspects of the context in which they work and their relationships with others to identify features of successful school leadership. This article reports on findings from a study into outstanding leadership in primary education using Q-methodology. The perceptions of head teachers, deputy head teachers, governors and academics with personal experience of leadership in English primary schools were gathered using Q-sort and analysed with PQ software. Overall, the analysis identified very strong agreement over six statements from a Q-set of 23 statements of outstanding leadership. There were subtle differences between urban and rural school settings.